A controllable etching supramolecular hydrogel based on metal ions. Issue 10 (26th February 2018) - Luan, Tianxiang; Ma, Mingfang; Xing, Pengyao; Wang, Yajie; Yang, Minmin; Zhang, Yimeng; An, Wei; Cheng, Qiuhong; Hao, Aiyou
Abstract : We report an interesting gel-etching system in which a gel can be etched with corresponding etching rates and color changes when different types of etching molecules are added to the gel. Abstract : We report an interesting gel-etching system in which a gel can be etched with corresponding etching rates and color changes when different types of etching molecules are added to the gel. This gel system may have wide potential application in molecular recognition, pre-packaged, as well as other functional materials.